Association between oral microbiome and five types of respiratory infections: a two-sample Mendelian randomization study in east Asian population - He, Jiawei; Mao, Ningfeng; Lyu, Wenliang; Zhou, Shuhan; Zhang, Yang; Liu, Zhiyi; Xu, Zixuan (Frontiers in Microbiology, 2024)
Objective: To explore the causal relationship between the oral microbiome and specific respiratory infections including tonsillitis, chronic sinusitis, bronchiectasis, bronchitis, and pneumonia, assessing the impact of genetic variations associated with the oral microbiome.Methods: Mendelian randomization was used to analyze genetic variations, leveraging data from genome-wide association studies in an East Asian cohort to identify connections between specific oral microbiota and respiratory infections.Results: Our analysis revealed that Prevotella, Streptococcus, Fusobacterium, Pauljensenia, and Capnocytophaga play crucial roles in influencing respiratory infections. Prevotella is associated with both promoting bronchitis and inhibiting pneumonia and tonsillitis, with a mixed effect on chronic sinusitis. Streptococcus and Fusobacterium show varied impacts on respiratory diseases, with Fusobacterium promoting chronic sinusitis, bronchiectasis, and bronchitis. Conversely, Pauljensenia and Capnocytophaga are linked to reduced bronchitis and tonsillitis, and inhibited pneumonia and bronchitis, respectively. Discussion: These findings underscore the significant impact of the oral microbiome on respiratory health, suggesting potential strategies for disease prevention and management through microbiome targeting. The study highlights the complexity of microbial influences on respiratory infections and the importance of further research to elucidate these relationships.